2005
DOI: 10.1111/j.1460-9592.2004.01518.x
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance and analgesic efficacy of a new i.v. paracetamol solution in children after inguinal hernia repair

Abstract: A single infusion of i.v. paracetamol 15 mg.kg(-1) produced analgesia similar to a single infusion of propacetamol 30 mg.kg(-1) following inguinal hernia repair in children. Paracetamol i.v. 15 mg.kg(-1) was better tolerated at the injection site than propacetamol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(45 citation statements)
references
References 18 publications
5
40
0
Order By: Relevance
“…[6] In a clinical trial, comparing the analgesic efficacy of IV paracetamol after inguinal hernia repair in children. [13] Similar to our results, they found that no clinically significant abnormality in vital signs were observed with this new solution of paracetamol. Also, we did not observe any adverse effect of drug during IV administration.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…[6] In a clinical trial, comparing the analgesic efficacy of IV paracetamol after inguinal hernia repair in children. [13] Similar to our results, they found that no clinically significant abnormality in vital signs were observed with this new solution of paracetamol. Also, we did not observe any adverse effect of drug during IV administration.…”
Section: Discussionsupporting
confidence: 90%
“…[11,12,13] However, the optimum route of administration of acetaminophen is unclear, there are few studies directly comparing routes of delivery for actual analgesic effectiveness. [4,14] We chose to compare single doses of acetaminophen 15 mg/kg IV and 40 mg/kg per rectal as these are the often used doses associated with similar plasma levels.…”
mentioning
confidence: 99%
“…Assessments using the Smiley scale and VAS were performed separately at rest and in motion. Whenever the intensity of pain increased above 3 on a 10-point scale, a higher stage of the treatment scheme was used [17].…”
Section: Methodsmentioning
confidence: 99%
“…A greater initial dose followed by maintenance doses not exceeding recommended maximum daily doses is generally recommended. Peak plasma levels are rapidly achieved after oral ingestion, but there is a 1-2 h lag before the maximum therapeutic effect; the onset of analgesia after IV administration may be much faster [ 62 ]. As rectal bioavailability is much reduced and more variable than oral bioavailability, greater initial doses are recommended when this route is used except in the premature infant.…”
Section: Acetaminophen (Paracetamol)mentioning
confidence: 99%